The International monetary system : the next twenty-five years : symposium at Basle University to commemorate twenty-five years of Per Jacobsson lectures, June 12, 1988 - Bergsten Fred C. (New York : Per jacobsson foundation, 1988)
This book provides an insight into the IMF policy under the leadership of the per Jacobson. The lecture contains various research monetary analysis in projection for the next 25 years.
asm; 13/02/19
Loans
Keywords: International finance; International monetary fund